Transcriptional Regulation of Vih by Oct4 and Sox9 in Scylla paramamosain - Liao, Jiaqian; Zhang, Ziping; Jia, Xiwei; Zou, Zhihua; Liang, Keying; Wang, Yilei (Frontiers in Endocrinology, 2020)
Mud crab (Scylla paramamosain) is one of the most important marine culture crabs in China. However, the research on its reproductive regulation mechanism is not deep enough. Vitellogenesis-inhibiting hormone (VIH) is one of the crustacean hyperglycemia hormones (CHH), which plays an essential role in the regulation of gonadal development and maturation in crustaceans, and current studies on the regulation of Vih transcription in crabs are relatively rare. Our previous studies on the transcriptional regulation of mud crab Vih (SpVih) have proved that the binding site of Oct4/Sox9 transcription factor may be the key region for positively regulating the expression of SpVih. In this study, the EMSA experiment confirmed that the nuclear protein extracted from the eyestalk could bind to the key region of SpVih promoter, and these specific bindings were dependent on the presence of Oct4/Sox9 binding sites of the SpVih promoter. Two specific binding complex bands were detected in the Supershift group of EMSA Super-shift experiment by Oct4 and SoxE antibodies, further confirming the specific recognition between the transcription factor and the key regulatory region of SpVih. In vitro, Oct4 and Sox9 gene overexpression vectors and SpVih core promoter fragment vector were constructed and co-transfected into HEK293T cells. As a result, SpVih activity increased with the concentration of transcription factors. In vivo, Oct4 and Sox9 dsRNA were injected into the eyestalks of mud crab. The results showed that the expression level of SpVih decreased significantly after interference with Oct4 or Sox9, while the expression level of SpVtg in the ovary and hepatopancreatic were increased. Both in vitro and in vivo experiments showed that Oct4 and Sox9 had a positive regulatory effect on SpVih. The GST pulldown experiment was carried out by purified Oct4 and Sox9 proteins, and the results showed that there was an interaction between them. It was speculated that they regulated the expression of SpVih through the interaction. These results will help us to better understand the regulatory mechanism of SpVih gene, and hope to achieve the goal of promoting ovarian development and maturation of mud crab by controlling the key factors.